Pengaruh Dimensi Eco-Innovation Terhadap Kinerja Bisnis Sustainable pada UMKM Kreatif - Afifah Mahkota Putri; Keumala Hayati (Teewan Journal Solutions, 2025)
This study aims to analyze the influence of eco-innovation dimensions on sustainable business performance in creative MSMEs. Eco-innovation which includes products, processes, and environmental organizations is expected to improve sustainable business performance. Data were collected through a survey of creative MSME players in Indonesia and 119 data were obtained in the study. Data analysis wus conducted using multiple linear regression methods to test the influence between variables. The results showed that the dimensions of eco-innovation, both in terms of products, processes, and organizations, have a positive and significant influence on the sustainable business performance of creative MSMEs. The implementation of eco-innovation can improve operational efficiency, reduce environmental impacts, and strengthen market competitiveness. These findings provide insights for creative MSME players to prioritize sustainable aspects in running their business, along with market demands that are increasingly concerned about environmental issues.